Size-dependent aggregation of hydrophobic nanoparticles in lipid membranes. Issue 17 (24th April 2020) - Lavagna, Enrico; Barnoud, Jonathan; Rossi, Giulia; Monticelli, Luca
Abstract : Aggregation of hydrophobic spherical nanoparticles in lipid membranes depends on nanoparticle size. Nanoparticles of ∼3 nm sense and induce membrane curvature. Abstract : The aggregation of nanoparticles affects their reactivity, transport across biological membranes, uptake into cells, toxicity, and fate in the environment. In the case of membrane-embedded, hydrophobic nanoparticles the relationship between size and aggregation pattern is not well understood. Here, we explore this relationship for the case of spherically symmetrical nanoparticles using the MARTINI coarse-grained force field. We find that the free energy of dimerization depends strongly on nanoparticle size: the smallest molecules (mimicking C60 fullerene) aggregate only weakly, the largest ones form large three-dimensional aggregates causing major deformations in the host membrane, and the intermediate-sized particles show a tendency to form linear aggregates. Suppressing membrane undulations reduces very significantly aggregation, and substantially abolishes linear aggregation, suggesting a relationship between membrane curvature and aggregation geometry. At low concentration, when placed on membranes of variable curvature, the intermediate size nanoparticles move rapidly to high curvature regions – suggesting that they can sense membrane curvature. At high concentration, the same nanoparticles induce massive membrane deformations, without affecting the mechanical stability of the membrane – suggesting that they can generate membrane curvature.